Implementasi Sistem Monitoring Risiko Peningkatan Kadar Glukosa Darah Secara Non-Invasive Menggunakan Photodioda dan LED - Sarah Savira; Insani Abdi Bangsa; Lela Nurpulaela (LPPM Poltek ST Paul, 2021)
Diabetes Mellitus (DM) can be characterized by increasing levels of glucose in the blood. There are two types of methods that are often used to measure blood glucose levels, namely the invasive method and the non-invasive method. The invasive method is a method that requires a blood sample by making a cut on the finger and then the blood will be dripped on the blood strip, this tool is called a glucometer. Whereas in the non-invasive method, measuring glucose levels in the blood does not require a blood sample. In this study, blood glucose levels will be measured using a non-invasive method, using a photodiode as a light receiver and a red LED as a light emitter, so that blood glucose levels can be read through the measurement with the fingertip. The sensor readings will be processed in the Arduino Uno and then displayed on the LCD.